A process for preparing negative electrode material using natural graphite and waste batteries
In the process of preparing negative electrode materials in natural graphite and waste batteries, technical means such as flotation, spherification, coating pre-carbonization and high-temperature impurity removal and modification treatment are used to solve the problems of high energy consumption, difficulty in removing impurities and environmental pollution in the existing technology, and efficient and environmentally friendly negative electrode material preparation is achieved to meet the high requirements of lithium-ion batteries for negative electrode materials.
Patent Information
- Application Number
- CN202411649459.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2044-11-19
AI Technical Summary
When using natural graphite and used batteries to prepare negative electrode materials, the prior art has problems such as high energy consumption, difficulty in removing impurities, environmental pollution and equipment corrosion.
The process of preparing negative electrode materials using natural graphite and waste batteries includes natural graphite pretreatment, waste battery pretreatment, flotation, spherification, coating pre-carbonization, impurity removal and modification treatment and finished product preparation. The shape and performance of graphite particles are improved by sphericalization and coating pre-carbonization, and the integrated treatment of decompression and modification is performed using Freon gas at high temperatures to remove impurities and improve the electrochemical properties of graphite.
The efficient preparation of negative electrode materials is achieved, the recycling rate of resources is improved, energy consumption and cost are reduced, and the pollution to the environment is reduced. The resulting negative electrode materials are more purified and have excellent electrochemical performance.
Smart Images

Figure SMS_8 
Figure SMS_9 
Figure SMS_10
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of negative electrode material preparation, and specifically relates to a process for preparing negative electrode materials by utilizing natural graphite and waste batteries. Background Art
[0002] Negative electrode materials are raw materials that constitute the negative electrode in the battery. They play the role of storing and releasing energy in the battery, and mainly affect the cycle performance and other indicators of lithium batteries. Negative electrode materials can be divided into two categories: carbon materials and non-carbon materials. Carbon materials include natural graphite, artificial graphite, mesophase carbon microbeads, soft carbon, hard carbon, carbon nanotubes, graphene, etc. Non-carbon materials include titanium-based materials, silicon-based materials, tin-based materials, nitrides and metallic lithium, etc.
[0003] As an important negative electrode material, natural graphite is widely used in the field of lithium-ion batteries. Natural graphite has physical properties such as small thermal expansion coefficient, high thermal conductivity, high temperature resistance, as well as excellent conductivity, lubricity, plasticity, chemical stability and thermal shock resistance, making it an ideal choice for negative electrode materials of lithium-ion batteries.
[0004] With the widespread use of lithium-ion batteries, the recycling of waste batteries has become the focus of environmental protection and resource reuse. The graphite negative electrode materials in waste lithium-ion batteries are often overlooked, and these waste graphites not only cause environmental pollution, but also have high recycling value.
[0005] In the prior art, the methods for preparing negative electrode materials from natural graphite and waste batteries include: mechanical crushing and heat treatment, acid leaching, sulfuric acid curing-acid leaching, electrochemical method, etc., but there are also the following disadvantages:
[0006] 1. Mechanically crush the used batteries, remove the conductive agent, binder and thickener by heat treatment, and then regenerate them. The disadvantage of this method is that it consumes a lot of energy and may not completely remove all impurities, affecting the performance of the negative electrode material.
[0007] 2. Use acidic solutions such as sulfuric acid and hydrochloric acid to leach metal impurities in waste batteries to purify graphite. The disadvantage of this method is that it will pollute the environment and corrode the equipment;
[0008] 3. First, the negative electrode material is solidified by sulfuric acid, and then the negative electrode material is recovered by acid leaching. The graphite obtained by this method has higher purity, but there are also problems of environmental pollution and equipment corrosion;
[0009] 4. Separating graphite from copper foil by electrochemical reaction, without involving corrosive reagents such as acid and alkali. The disadvantage of this method is that it can only separate the current collector copper and graphite active materials, and the problem of recycling valuable metals remains to be solved. Summary of the invention
[0010] In view of the above problems, the present invention provides a process for preparing negative electrode materials using natural graphite and waste batteries, which achieves efficient preparation of negative electrode materials, improves the recycling rate of resources, and reduces the impact on the environment.
[0011] To achieve the above object, the technical solution adopted by the present invention is:
[0012] A process for preparing negative electrode materials using natural graphite and waste batteries comprises the following steps:
[0013] Step 1, natural graphite pretreatment: the graphite ore raw material is initially crushed by a crushing device, and then ground by a ball mill to obtain graphite powder;
[0014] Step 2, pretreatment of waste batteries: first perform deep discharge treatment on the waste lithium batteries, then disassemble and separate the positive and negative electrode materials, and then obtain relatively pure negative electrode materials through crushing, pyrolysis and physical separation;
[0015] Step 3, flotation: the graphite powder obtained in step 1 and the negative electrode material obtained in step 2 are mixed, added into water to form a slurry, and then a collector, a foaming agent and a regulator are added to prepare the slurry, stirred for 10-30 minutes, and then the prepared slurry is sent to a flotation machine for flotation operation, and graphite foam is collected to obtain graphite purification slurry, and finally purified graphite powder is obtained by dehydration and drying;
[0016] Step 4, spheroidization: putting the purified graphite powder obtained in step 3 into a spheroidization device to obtain spherical graphite particles with a particle size of 13-28 μm;
[0017] Step 5, coating pre-carbonization: coating the spherical graphite particles obtained in step 4 with asphalt, then carbonizing them at high temperature, and naturally cooling them to obtain carbonized graphite particles;
[0018] Step 6, impurity removal and modification treatment: the carbonized graphite particles obtained in step 5 are placed in a carbon-carbon rotary kiln, and freon gas is passed through the rotary kiln at 2000-2200° C. to perform an integrated impurity removal and modification treatment to obtain a graphite material;
[0019] Step 7, finished product preparation: the graphite material obtained in step 6 is screened, demagnetized and packaged to obtain a finished negative electrode material.
[0020] In a preferred implementation, in step 1, the graphite powder is initially crushed to a particle size of 15-30 mm, ground to a particle size of 250-500 μm, and has a purity of 40-50%.
[0021] In a preferred embodiment, the physical separation process in step 2 includes screening, magnetic separation, gravity separation and color separation, and the purity of the relatively pure negative electrode material is 85-90%.
[0022] In a preferred implementation, the collector in step 3 includes kerosene or sodium dodecylbenzene sulfonate, the foaming agent is pine oil, and the adjusting agent includes one of quicklime, polyaluminium chloride and polyacrylamide.
[0023] In a preferred implementation, the mass ratio of the collector, frother and regulator in step 3 is 1:1-2:1-2, and the total amount of the collector, frother and regulator added accounts for 0.1-1% of the mass of the raw materials in the ore slurry.
[0024] In a preferred embodiment, the purity of the purified graphite powder in step 3 is 95-96%.
[0025] In a preferred embodiment, the high temperature carbonization temperature in step 5 is 500-800°C.
[0026] In a preferred implementation, in step 6, the Freon gas is introduced from the tail of the carbon-carbon rotary kiln, the ratio of the introduced amount to the amount of carbonized graphite particles is 1L:50-200g, and the Freon gas flow rate is 0.6-2.5L / min.
[0027] In a preferred implementation, the time for the integrated treatment of impurity removal and modification in step 6 is 20-120 minutes.
[0028] Compared with the prior art, the present invention has the following beneficial effects: (1) the present invention uses natural graphite and waste batteries as raw materials, effectively recycles and utilizes resources, reduces resource waste, and optimizes the entire process flow. By integrating impurity removal and modification, the process steps are reduced, which not only improves the preparation efficiency of negative electrode materials, reduces energy consumption and costs, but also reduces environmental pollution during the treatment process, avoids the emission of harmful substances caused by the traditional acid leaching method, and obtains a negative electrode material with higher purity and excellent electrochemical performance, which can meet the high requirements of lithium-ion batteries for negative electrode materials;
[0029] (2) The present invention places graphite particles into a carbon-carbon rotary kiln for integrated impurity removal and modification, thereby achieving simultaneous impurity removal and modification. Freon gas is introduced for impurity removal, and decomposed into chlorine and fluorine at high temperature. Since most metal halides have very low melting points and boiling points, some impurities that are difficult to vaporize, such as B, Al, Fe, Si, Ti, etc., can be discharged through chlorination and fluorination methods, and most impurities can be directly removed to improve the purity of graphite. The carbon-carbon rotary kiln used is resistant to high temperature corrosion, can support the introduction of Freon at high temperature, and can also rotate, so that the graphite particles can fully contact and react with Freon, thereby better removing impurities. The equipment combined with the process can achieve the integrated impurity removal and modification treatment by introducing Freon gas at high temperature.
[0030] The reaction principle of removing impurities by introducing Freon at high temperature is as follows:
[0031]
[0032]
[0033]
[0034]
[0035]
[0036]
[0037] .
[0038] The melting and boiling points of fluoride and chloride impurities generated by reactions in graphite are listed below:
[0039] Table 1
[0040]
[0041] Table 2
[0042] DETAILED DESCRIPTION
[0043] In order to enable those skilled in the art to better understand the technical solution, the present invention is described in detail below in conjunction with embodiments. The description in this section is only exemplary and explanatory and should not have any limiting effect on the scope of protection of the present invention.
[0044] The carbon-carbon rotary kiln used in the following embodiments is an ultra-high temperature continuous rotary kiln disclosed in patent CN117213225A.
[0045] Embodiment 1:
[0046] A process for preparing negative electrode materials using natural graphite and waste batteries comprises the following steps:
[0047] Step 1, natural graphite pretreatment: the graphite ore raw material is initially crushed to a particle size of 15-20 mm using a crushing device, and then ground to a particle size of 250-360 μm using a ball mill to obtain graphite powder, and the purity of the graphite powder is 45%;
[0048] Step 2, pretreatment of waste batteries: the waste lithium batteries are first subjected to deep discharge treatment, and then disassembled to separate the positive and negative electrode materials, and then subjected to crushing, pyrolysis, and physical sorting treatments. The physical sorting treatments include screening, magnetic separation, gravity separation, and color separation to obtain relatively pure negative electrode materials. The purity of the relatively pure negative electrode materials is 87%;
[0049] Step 3, flotation: the graphite powder obtained in step 1 and the negative electrode material obtained in step 2 are mixed, added into water to form a slurry, and then a collector, a foaming agent and a regulator are added to prepare the slurry, stirred for 30 minutes, and then the prepared slurry is sent to a flotation machine for flotation operation, and graphite foam is collected to obtain a graphite purification slurry, and finally purified graphite powder is obtained by dehydration and drying, wherein the purity of the purified graphite powder is 95.6%, the collector comprises kerosene or sodium dodecylbenzene sulfonate, the foaming agent is pine oil, and the regulator comprises one of quicklime, polyaluminum chloride and polyacrylamide, the mass ratio of the collector, the foaming agent and the regulator to prepare the slurry is 1:2:2, and the total amount of the collector, the foaming agent and the regulator added accounts for 0.6% of the mass of the raw materials in the slurry;
[0050] Step 4, spheroidization: putting the purified graphite powder obtained in step 3 into a spheroidization device to obtain spherical graphite particles with a particle size of 20-28 μm;
[0051] Step 5, coating pre-carbonization: the spherical graphite particles obtained in step 4 are coated with asphalt, and then carbonized at high temperature, the high temperature carbonization temperature is 750° C., and naturally cooled to obtain carbonized graphite particles;
[0052] Step 6, impurity removal and modification treatment: the carbonized graphite particles obtained in step 5 are placed in a carbon-carbon rotary kiln, and a freon gas is introduced into the rotary kiln at 2200°C for an integrated treatment of impurity removal and modification for 20 minutes. The freon gas is introduced from the tail of the carbon-carbon rotary kiln, and the ratio of the amount of the introduced gas to the amount of the carbonized graphite particles is 1L:100g, and the freon gas flow rate is 1.3L / min, to obtain a graphite material;
[0053] Step 7, finished product preparation: the graphite material obtained in step 6 is screened, demagnetized and packaged to obtain a finished negative electrode material.
[0054] Embodiment 2:
[0055] A process for preparing negative electrode materials using natural graphite and waste batteries comprises the following steps:
[0056] Step 1, natural graphite pretreatment: the graphite ore raw material is initially crushed to a particle size of 20-30 mm using a crushing equipment, and then ground to a particle size of 380-500 μm using a ball mill to obtain graphite powder, and the purity of the graphite powder is 40%;
[0057] Step 2, pretreatment of waste batteries: the waste lithium batteries are first subjected to deep discharge treatment, and then disassembled to separate the positive and negative electrode materials, and then subjected to crushing, pyrolysis, and physical sorting treatments. The physical sorting treatments include screening, magnetic separation, gravity separation, and color separation to obtain relatively pure negative electrode materials. The purity of the relatively pure negative electrode materials is 90%;
[0058] Step 3, flotation: the graphite powder obtained in step 1 and the negative electrode material obtained in step 2 are mixed, added into water to form a slurry, and then a collector, a foaming agent and a regulator are added to prepare the slurry, stirred for 25 minutes, and then the prepared slurry is sent to a flotation machine for flotation operation, and graphite foam is collected to obtain a graphite purification slurry, and finally purified graphite powder is obtained by dehydration and drying, wherein the purity of the purified graphite powder is 95.3%, the collector comprises kerosene or sodium dodecylbenzene sulfonate, the foaming agent is pine oil, and the regulator comprises one of quicklime, polyaluminum chloride and polyacrylamide, the mass ratio of the collector, the foaming agent and the regulator to prepare the slurry is 1:1:1, and the total amount of the collector, the foaming agent and the regulator added accounts for 1% of the mass of the raw materials in the slurry;
[0059] Step 4, spheroidization: putting the purified graphite powder obtained in step 3 into a spheroidization device to obtain spherical graphite particles with a particle size of 13-18 μm;
[0060] Step 5, coating pre-carbonization: the spherical graphite particles obtained in step 4 are coated with asphalt, and then carbonized at high temperature, the high temperature carbonization temperature is 500° C., and naturally cooled to obtain carbonized graphite particles;
[0061] Step 6, impurity removal and modification treatment: the carbonized graphite particles obtained in step 5 are placed in a carbon-carbon rotary kiln, and freon gas is passed through the rotary kiln at 2000°C for an integrated treatment of impurity removal and modification for 120 minutes. The freon gas is introduced from the tail of the carbon-carbon rotary kiln, and the ratio of the amount of the introduced gas to the amount of the carbonized graphite particles is 1L:200g, and the freon gas flow rate is 2.5L / min, to obtain a graphite material;
[0062] Step 7, finished product preparation: the graphite material obtained in step 6 is screened, demagnetized and packaged to obtain a finished negative electrode material.
[0063] Embodiment 3:
[0064] A process for preparing negative electrode materials using natural graphite and waste batteries comprises the following steps:
[0065] Step 1, natural graphite pretreatment: the graphite ore raw material is initially crushed to a particle size of 15-25 mm using a crushing device, and then ground to a particle size of 300-450 μm using a ball mill to obtain graphite powder, and the purity of the graphite powder is 50%;
[0066] Step 2, pretreatment of waste batteries: the waste lithium batteries are first subjected to deep discharge treatment, and then disassembled to separate the positive and negative electrode materials, and then subjected to crushing, pyrolysis, and physical sorting treatments. The physical sorting treatments include screening, magnetic separation, gravity separation, and color separation to obtain relatively pure negative electrode materials. The purity of the relatively pure negative electrode materials is 85%;
[0067] Step 3, flotation: the graphite powder obtained in step 1 and the negative electrode material obtained in step 2 are mixed, added into water to form a slurry, and then a collector, a foaming agent and a regulator are added to prepare the slurry, stirred for 10 minutes, and then the prepared slurry is sent to a flotation machine for flotation operation, and graphite foam is collected to obtain a graphite purification slurry, and finally purified graphite powder is obtained by dehydration and drying, wherein the purity of the purified graphite powder is 96%, the collector comprises kerosene or sodium dodecylbenzene sulfonate, the foaming agent is pine oil, and the regulator comprises one of quicklime, polyaluminum chloride and polyacrylamide, the mass ratio of the collector, the foaming agent and the regulator to prepare the slurry is 1:2:1, and the total amount of the collector, the foaming agent and the regulator added accounts for 0.3% of the mass of the raw materials in the slurry;
[0068] Step 4, spheroidization: putting the purified graphite powder obtained in step 3 into a spheroidization device to obtain spherical graphite particles with a particle size of 15-25 μm;
[0069] Step 5, coating pre-carbonization: the spherical graphite particles obtained in step 4 are coated with asphalt, and then carbonized at high temperature, the high temperature carbonization temperature is 800° C., and naturally cooled to obtain carbonized graphite particles;
[0070] Step 6, impurity removal and modification treatment: the carbonized graphite particles obtained in step 5 are placed in a carbon-carbon rotary kiln, and a Freon gas is introduced into the rotary kiln at 2150°C for an integrated treatment of impurity removal and modification for 68 minutes. The Freon gas is introduced from the tail of the carbon-carbon rotary kiln, and the ratio of the amount of the introduced gas to the amount of the carbonized graphite particles is 1L:80g, and the Freon gas flow rate is 0.8L / min, to obtain a graphite material;
[0071] Step 7, finished product preparation: the graphite material obtained in step 6 is screened, demagnetized and packaged to obtain a finished negative electrode material.
[0072] Comparative Example 1:
[0073] The difference between this comparative example and Example 1 is that the negative electrode material is prepared by traditional technology. After the graphite powder is purified and spheroidized, it is not directly coated with asphalt for pre-carbonization. Instead, hydrofluoric acid + hydrochloric acid is added to purify and dry the graphite impurities to obtain a graphite powder with a graphite purity of 99.95%. Subsequently, asphalt coating and pre-carbonization are continued, and then the graphite powder is placed in a roller kiln + Acheson furnace for high-temperature modification. The impurities are not removed by Freon, and the impurity removal and modification are carried out separately. The specific acid leaching impurity removal process is: spherical graphite particles are put into a dissolving tank, and a de-impurity solution mixed with hydrochloric acid and hydrofluoric acid is added. The mass ratio of each component is 1:1. For example: 38 kg of hydrochloric acid (concentration of 31%), 22 kg of hydrofluoric acid (concentration of 41%), and then add 70 L of pure water, the mass ratio of spherical graphite particles to impurity removal liquid is 1:2, the temperature of the dissolution tank is adjusted to 100°C, and the reaction is maintained for 24 hours. The reacted graphite solution is filtered through a filter press, and the wet material after filtration is added with purified water for washing and mixing, and then filtered again through a filter press. The wet graphite material after filtration is transported to a flash dryer for drying, and the drying temperature is controlled at 200°C. The dried graphite powder is subjected to magnetic adsorption to remove possible residual magnetic metal impurities to obtain graphite powder.
[0074] Comparative Example 2:
[0075] The difference between this comparative example and Example 1 is that, when performing the integrated impurity removal and modification treatment in step 6, the carbonized graphite particles are placed in a roller kiln and an Acheson furnace, and then Freon is introduced to perform impurity removal and modification at the same time. Other technical contents are the same as those in Example 1.
[0076] The finished negative electrode materials prepared in Examples 1-3 and Comparative Examples 1-2 were tested for components and compared with the raw materials for impurities. The results are shown in the following table.
[0077] Table 3
[0078]
[0079] The product parameters of Example 1 were tested, and the test results are shown in the following table.
[0080] Table 4
[0081]
[0082] The process for preparing the negative electrode material in Example 1 was compared with the traditional process in Comparative Example 1. The comparison results are shown in the following table.
[0083] Table 5
[0084]
[0085] It should be noted that, in this article, the terms: include, contain and any other variants are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. Specific examples are used in this article to illustrate the principle and implementation of the technical solution of the present invention. The above examples are only used to help understand the method of the present invention and its core idea. The above is only a preferred implementation of the present invention. It should be pointed out that due to the limitations of textual expression and the objective existence of infinite specific structures, for ordinary technicians in this technical field, without departing from the principle of the present invention, several improvements, modifications or changes can be made, and the above technical features can also be combined in an appropriate manner; these improvements, modifications, changes or combinations, or the direct application of the concept and technical solution of the present invention to other occasions without improvement, should be regarded as the protection scope of the present invention.
Claims
1. A process for preparing negative electrode materials using natural graphite and waste batteries, characterized in that: The following steps are involved: Step 1, natural graphite pretreatment: the graphite ore raw material is initially crushed by a crushing device, and then ground by a ball mill to obtain graphite powder; Step 2, pretreatment of waste batteries: first perform deep discharge treatment on the waste lithium batteries, then disassemble and separate the positive and negative electrode materials, and then obtain relatively pure negative electrode materials through crushing, pyrolysis and physical separation; Step 3, flotation: the graphite powder obtained in step 1 and the negative electrode material obtained in step 2 are mixed, added into water to form a slurry, and then a collector, a foaming agent and a regulator are added to prepare the slurry, stirred for 10-30 minutes, and then the slurry after preparation is sent to a flotation machine for flotation operation, and graphite foam is collected to obtain a graphite purification slurry, and finally purified graphite powder is obtained by dehydration and drying, wherein the collector comprises kerosene or sodium dodecylbenzene sulfonate, the foaming agent is pine oil, and the regulator comprises one of quicklime, polyaluminum chloride and polyacrylamide; the mass ratio of the collector, the foaming agent and the regulator to prepare the slurry is 1:1-2:1-2, and the total amount of the collector, the foaming agent and the regulator added accounts for 0.1-1% of the mass of the raw materials in the slurry; Step 4, spheroidization: putting the purified graphite powder obtained in step 3 into a spheroidization device to obtain spherical graphite particles with a particle size of 13-28 μm; Step 5, coating pre-carbonization: coating the spherical graphite particles obtained in step 4 with asphalt, then carbonizing them at high temperature, and naturally cooling them to obtain carbonized graphite particles; Step 6, impurity removal and modification treatment: the carbonized graphite particles obtained in step 5 are placed in a carbon-carbon rotary kiln, and a Freon gas is introduced into the rotary kiln at 2000-2200° C. for integrated impurity removal and modification treatment to obtain a graphite material, wherein the Freon gas is introduced from the tail of the carbon-carbon rotary kiln, and the ratio of the amount of the introduced gas to the amount of the carbonized graphite particles is 1L:50-200g, and the Freon gas flow rate is 0.6-2.5L / min; Step 7, finished product preparation: the graphite material obtained in step 6 is screened, demagnetized and packaged to obtain a finished negative electrode material.
2. The process for preparing negative electrode materials using natural graphite and waste batteries according to claim 1, characterized in that: In the step 1, the graphite powder is initially crushed to a particle size of 15-30 mm, and ground to a particle size of 250-500 μm, and the purity of the graphite powder is 40-50%.
3. The process for preparing negative electrode material by using natural graphite and waste batteries according to claim 1, characterized in that: The physical separation process in step 2 includes screening, magnetic separation, gravity separation and color separation, and the purity of the relatively pure negative electrode material is 85-90%.
4. The process for preparing negative electrode materials using natural graphite and waste batteries according to claim 1, characterized in that: The purity of the graphite powder purified in step 3 is 95-96%.
5. The process for preparing negative electrode material by using natural graphite and waste batteries according to claim 1, characterized in that: The high temperature carbonization temperature in step 5 is 500-800°C.
6. The process for preparing negative electrode materials using natural graphite and waste batteries according to claim 1, characterized in that: The time for the integrated treatment of impurity removal and modification in step 6 is 20-120 minutes.
Citation Information
Patent Citations
Method for regenerating graphite in waste battery
CN117003235A
Agent group for flotation separation of carbon-coated lithium iron phosphate and graphite and application
CN117181452A